2002
DOI: 10.1002/1522-2683(200210)23:19<3253::aid-elps3253>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The protonation of an aqueous solution of two ampholytes AH and BH next to a gel buffered by immobilized acid moieties IH has been studied by finite element simulation in an iterative scheme. A ten species model has been formulated, taking into account transient diffusion and equilibrium kinetics of the two amphoteric species AH and BH, of water and of the immobilized species IH. This model has been developed to illustrate the pH evolution between an ampholyte solution and an Immobiline gel, and to study the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The principle is to place a sample in a liquid chamber which is positioned on top of an IPG gel. Theoretical calculations and modelling have shown that the protonation of an ampholyte occurs in the thin layer of solvation closed to the IPG gel/solution interface (Arnaud et al, 2002). Upon application of a voltage gradient, perpendicularly to the liquid chamber, the electric field penetrates into the channel and extracts all charged species (those having pI values above and below the pH of the IPG gel), thus vacating them from the sample cup.…”
Section: Miniaturized Isoelectric Separation Devicesmentioning
confidence: 99%
“…The principle is to place a sample in a liquid chamber which is positioned on top of an IPG gel. Theoretical calculations and modelling have shown that the protonation of an ampholyte occurs in the thin layer of solvation closed to the IPG gel/solution interface (Arnaud et al, 2002). Upon application of a voltage gradient, perpendicularly to the liquid chamber, the electric field penetrates into the channel and extracts all charged species (those having pI values above and below the pH of the IPG gel), thus vacating them from the sample cup.…”
Section: Miniaturized Isoelectric Separation Devicesmentioning
confidence: 99%
“…A previous model based on diffusion-equilibria equations had already been developed to study the influence of the buffering capacity of the gel at the solution/gel interface [26]. The present work studies the effects of the nonuniform conductivity distribution in the cell on the diffusion-…”
Section: Numerical Modelmentioning
confidence: 99%
“…In Off-Gel  electrophoresis, the biological sample to be purified is filled in a flowchamber [25,26] or in static multiwells [27], which are positioned on top of an IPG gel. The pH at the bottom of the chamber is chosen to be close to the pI of the proteins to be isolated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The new instrument was shown to perform quite well in collecting proteome subfractions of very precise pI intervals, void of contamination from adjacent pI species [16][17][18]. An interesting variant of this approach is off-gel IEF in multicompartment devices [19][20][21]. If a series of chambers (up to 20), containing the proteome sample to be subfractionated, are placed directly on top of an IPG gel, in any desired pH interval, which is subjected to a voltage gradient, the sample proteins will move along the IPG migration path till reaching their pI value and thus collecting, at null surface charge, into the cup standing directly over the IPG gel segment titrating such species to their respective pI value.…”
Section: Introductionmentioning
confidence: 99%